Controversies and open questions in the definitions and classification of the hypereosinophilic syndromes and eosinophilic leukemias - Valent, Peter; Horny, Hans-Peter; Reiter, Andreas (Seminars in hematology, 2012)
Eosinophilia is frequently detectable in certain myeloid neoplasms and various reactive conditions, but it may also occur in the absence of an apparent underlying disease, or, rarely, as a paraneoplastic feature with solid tumors. In myeloid neoplasms, eosinophils are considered to belong to the malignant clone in most cases, whereas in all other conditions, eosinophilia is a reactive process triggered by eosinopoietic cytokines. Excessive accumulation of eosinophils, also termed hypereosinophilia (HE), is typically seen in eosinophilic leukemias, but it may also occur in other neoplasms and reactive disorders. HE-related end organ damage may develop in patients with reactive HE but also in those with hematologic malignancies. During the past few years, our knowledge about HE and HE-related organ damage in hematologic and nonhematologic disorders has improved considerably. Moreover, proposals for the definition and classification of eosinophil disorders have been generated by various expert groups and by the World Health Organization (WHO). However, several questions related to eosinophils and HE remain open, and many aspects of the definition and classification of eosinophil disorders and related pathologies remain controversial. In the current article, these open issues are discussed with special reference to the 2008 WHO classification of myeloid neoplasms and other classifications proposed by immunologists and various expert panels, as well as definitions and criteria recently proposed in a multidisciplinary consensus proposal.
Gesehen am 18.02.2019